The Cambridge handbook of second language acquisition - Herschensohn, Julia Rogers, 1945-; Young-Scholten, Martha (Cambridge : Cambridge University Press, 2013)
What is language and how can we investigate its acquisition by children or adults? What perspectives exist from which to view acquisition? What internal constraints and external factors shape acquisition? What are the properties of interlanguage systems? This comprehensive 31-chapter handbook is an authoritative survey of second language acquisition (SLA). Its multi-perspective synopsis on recent developments in SLA research provides significant contributions by established experts and widely recognized younger talent. It covers cutting edge and emerging areas of enquiry not treated elsewhere in a single handbook, including third language acquisition, electronic communication, incomplete first language acquisition, alphabetic literacy and SLA, affect and the brain, discourse and identity. Written to be accessible to newcomers as well as experienced scholars of SLA, the Handbook is organised into six thematic sections, each with an editor-written introduction.
Introduction / Julia Herschensohn and Martha Young-Scholten -- Part I: Theory and practice -- Theories of language from a critical perspective / Jan Koster -- History of the study of second language acquisition / Margaret Thomas -- Theoretical approaches / Florence Myles -- Scope and research methodologies / Melinda Whong and Clare Wright -- Part II: Internal ingredients -- The role of the native language / Claire Foley and Suzanne Flynn -- Learning mechanisms and automatization / Richard Towell -- Generative approaches and the poverty of the stimulus / Bonnie D. Schwartz and Rex A. Sprouse -- Learner internal psychological factors / Jean-Marc Dewaele -- Alphabetic literacy and adult SLA / Elaine Tarone, Kit Hansen and Martha Bigelow -- Part III: External ingredients -- Negotiated input and output/interaction / Mar del Pilar Garc Mayo and Eva Alc Soler -- Second language identity construction / Elizabeth R. Miller and Ryuko Kubota -- Socialization / Georges Daniel Vonique -- Variation / Vera Regan -- Electronic interaction and resources / Astrid Ensslin and Cedric Krummes -- Part IV: Biological factors -- Age related effects / Julia Herschensohn -- Childhood second language acquisition / Belma Haznedar and Elena Gavruseva -- Incomplete L1 acquisition / Silvina Montrul -- Third language acquisition / Jason Rothman, Jennifer Cabrelli Amaro and Kees de Bot -- Language processing / Alice Foucart and Cheryl Frenck-Mestre -- Affect and the brain / Andrea Mates and Anna Joaquin -- Part V: Properties of interlanguage systems -- The lexicon / James Milton and Giovanna Donzelli -- Semantics / Laurent Dekydtspotter -- Discourse and pragmatics / Roumyana Slabakova -- Morphosyntax / Tania Ionin -- Phonology and speech / Ellen Broselow and Yoonjung Kang -- Part VI: Models of development -- Explaining change in transition grammars / Michael Sharwood Smith, John Truscott and Roger Hawkins -- Stage-like development and organic grammar / Anne Vainikka and Martha Young-Scholten -- Emergentism, connectionism and complexity / Randal Holme -- Input, input processing and focus on form / Joe Barcroft and Wynne Wong -- Sociocultural theory and the zone of proximal development / Amy Snyder Ohta -- Nativelike and non-nativelike attainment / Donna Lardiere.
Includes bibliographical references and index.
Keywords: Second language acquisition